A Research Study Examining the Dynamics of Risk and Return Through the Lens of Behavioral Finance, Focusing on the Psychological Factors influencing decision-making in equity market investments. - Nitin Kumar Chauhan and Prof. Manas Pandey (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The rapid expansion of the Indian stock market can be attributed to the processes of liberalization, privatization, and globalization, alongside a rising global demand and supply. This growth has necessitated substantial capital investment to establish new business ventures that meet the needs of this expansive market. The equity market is crucial in providing the funds required for these initiatives. Key growth indicators, such as GDP, national income, and per capita income, are significantly affected by the contributions of the equity market. Furthermore, it plays a vital role in facilitating long-term capital growth and controlling inflation, which are essential for the healthy performance of the financial market. However, the effective operation of both the financial and equity markets is largely determined by the investment choices made by investors. It is often observed that investors' reactions are influenced by socio-economic, cultural, and psychological factors that may arise within society. The effects of these reactions manifest in the investment decisions made in the equity market. Any changes in these aforementioned factors can lead to corresponding impacts on the country's economy, highlighting the direct or indirect relationship between investment activities and external events. The lack of research in understanding investor behavior and decision-making strategies necessitates further investigation into how investors approach their decisions regarding investments. The current study aims to illuminate the behavioral factors that predominantly influence investment decisions and their subsequent effects on the equity market. Data for this analysis was collected from 1,100 individual investors in Varanasi through a meticulously designed questionnaire. Statistical analyses were conducted to enhance the factual understanding of the research study. The results of these analyses indicate that behavioral factors, including heuristics, prospect theory, and market dynamics, significantly affect investors' decision-making processes. This study highlights the influence of behavioral finance on investment choices and its implications for the equity market. Additionally, based on the research findings, the study offers a series of recommendations for investors.